Pengaruh Pengembangan Kompetensi, Distribusi Pekerjaan Dan Pengawasan Internal Terhadap Kinerja ASN Pada Perwakilan BPKP Provinsi Riau - Simbolon, Betric; Meilani, Nur Laila (Peneliti.net, 2023)
The image of employee performance in this country is occasionally branded with a lack of professionalism, an unvaried work culture. Meanwhile, performance by government employees in Indonesia is directed at the public interest, accelerating services that prioritize public satisfaction. Such is the case with the Financial and Development Supervisory Agency (BPKP) of Riau Province, where this study is intended to test employee performance. The test is intended to determine how the influence of competency development, job distribution and internal control on performance. The independent variable in this writing is competency development, job distribution and internal supervision with the dependent variable being employee performance. The method used in this study is a random sampling method which then uses the IBM SPSS 23 instrument to process data. The results in the research that has been conducted show indicators that competency development affects employee performance as evidenced by a calculated t value of 3.947; The distribution of competency work affects employee performance as evidenced in the calculated t value of 3.676; And internal supervision affects employee performance as evidenced by a calculated t value of 4.231. So it was concluded that competency development, job distribution and internal supervision have a simultaneous influence on employee performance according to the R square result of 0.686 which means that 68.6% of the performance of ASN employees in the Riau BPKP Representative is influenced by the variables studied and the rest are influenced by other variables that are not studied by the author.